2022
DOI: 10.1021/acs.est.2c01393
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Mechanisms of Copper Oxide Nanoparticles with Regard to Arsenic Availability in Soil–Rice Systems: Adsorption Behavior and Microbial Response

Abstract: Copper oxide nanoparticles (CuO NPs) are widely used as fungicides in agriculture. Arsenic (As) is a ubiquitous contaminant in paddy soil. The present study was focused on the adsorption behavior of CuO NPs with regard to As as well as the characteristics of the microbial community changes in As-contaminated soil–rice systems in response to CuO NPs. The study found that CuO NPs could be a temporary sink of As in soil; a high dose of CuO NPs promoted the release of As from crystalline iron oxide, which increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 92 publications
1
8
0
Order By: Relevance
“…This association is noteworthy because colloid- and nanoparticle-bound As are expected to be highly mobile and quite stable over significant distances, ,, enhancing its movement from As-contaminated paddy soils to an adjacent aquifer and surface water. , In addition to the As transport, the association of As with colloid- and nanoparticle OM–Fe may impact arsenic bioavailability in soil–rice systems by bypassing adsorption on immobile solids, , such as iron plaques that are dominated by Fe (oxyhydr)­oxides . Previous studies have demonstrated that the introduction of engineered nanoparticles to rice paddy soils altered As bioavailability and its accumulation in rice . However, the role of those naturally occurring Fe–OM–As colloids and nanoparticles in rice As uptake, translocation, and accumulation remains unknown.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This association is noteworthy because colloid- and nanoparticle-bound As are expected to be highly mobile and quite stable over significant distances, ,, enhancing its movement from As-contaminated paddy soils to an adjacent aquifer and surface water. , In addition to the As transport, the association of As with colloid- and nanoparticle OM–Fe may impact arsenic bioavailability in soil–rice systems by bypassing adsorption on immobile solids, , such as iron plaques that are dominated by Fe (oxyhydr)­oxides . Previous studies have demonstrated that the introduction of engineered nanoparticles to rice paddy soils altered As bioavailability and its accumulation in rice . However, the role of those naturally occurring Fe–OM–As colloids and nanoparticles in rice As uptake, translocation, and accumulation remains unknown.…”
Section: Resultsmentioning
confidence: 99%
“…64 Previous studies have demonstrated that the introduction of engineered nanoparticles to rice paddy soils altered As bioavailability and its accumulation in rice. 31 However, the role of those naturally occurring Fe−OM−As colloids and nanoparticles in rice As uptake, translocation, and accumulation remains unknown. Soil drainage, which is typically performed toward the end of tillering to control excessive rice tillering and 1−2 weeks before harvest, will cause rapid coagulation of As-bearing colloids and a decrease of total As.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microorganisms are mainly involved in arsenic metabolism and biological transformation in soil through their functional genes related to arsenic cycling ( Abou-Shanab et al, 2022 ). The arsenic metabolism mediated by microbial functional genes, including arsenic redox ( aoxR , arxA , aioAB , and arsJ ), reduction ( arsC , gstB , and arrAB ), methylation and demethylation ( arsI and arsM ), and efflux ( arsP , arsK , and arsB ), is a determinant of arsenic bioavailability in soil and an important step of global arsenic geochemical cycling ( Zhu et al, 2017 ; Chen et al, 2020 ) that has been extensively reviewed ( Zhu et al, 2017 ; Wu et al, 2022a ). To explore these key functional genes, Zhao et al (2018) developed a high-throughput qPCR chip (AsChip) containing 81 primer sets targeting 19 arsenic-related genes, aiming to comprehensively detect those genes linked to the microbial cycling of arsenic.…”
Section: Introductionmentioning
confidence: 99%